Antioxidant Function and Metabolomics Study in Mice after Dietary Supplementation with Methionine. (21st October 2020) - Yu, Manrong; Chen, Hui; Liu, Pan; Yang, Mei; Zou, Leqin; Xiao, Dingfu
Abstract : The antioxidant function and metabolic profiles in mice after dietary supplementation with methionine were investigated. The results showed that methionine supplementation enhanced liver GSH-Px activity and upregulated Gpx1 expression in the liver and SOD1 and Gpx4 expressions in the jejunum. Nrf2/Keap1 is involved in oxidative stress, and the western blotting data exhibited that dietary methionine markedly increased Keap1 abundance, while failed to influence the Nrf2 signal. Metabolomics investigation showed that methionine administration increased 2-hydroxypyridine, salicin, and asparagine and reduced D-Talose, maltose, aminoisobutyric acid, and inosine 5'-monophosphate in the liver, which are widely reported to involve in oxidative stress, lipid metabolism, and nucleotides generation. In conclusion, our study provides insights into antioxidant function and liver metabolic profiles in response to dietary supplementation with methionine.